Mitochondrial Respiration-Dependent ANT2-UCP2 Interaction - Schiffer, Tomas A.; Löf, Liza; Gallini, Radiosa; Kamali-Moghaddam, Masood; Carlström, Mattias; Palm, Fredrik (Frontiers in Physiology, 2022)
Adenine nucleotide translocases (ANTs) and uncoupling proteins (UCPs) are known to facilitate proton leak across the inner mitochondrial membrane. However, it remains to be unravelled whether UCP2/3 contribute to significant amount of proton leak in vivo. Reports are indicative of UCP2 dependent proton-coupled efflux of C4 metabolites from the mitochondrial matrix. Previous studies have suggested that UCP2/3 knockdown (KD) contributes to increased ANT-dependent proton leak. Here we investigated the hypothesis that interaction exists between the UCP2 and ANT2 proteins, and that such interaction is regulated by the cellular metabolic demand. Protein-protein interaction was evaluated using reciprocal co-immunoprecipitation and in situ proximity ligation assay. KD of ANT2 and UCP2 was performed by siRNA in human embryonic kidney cells 293A (HEK293A) cells. Mitochondrial and cellular respiration was measured by high-resolution respirometry. ANT2-UCP2 interaction was demonstrated, and this was dependent on cellular metabolism. Inhibition of ATP synthase promoted ANT2-UCP2 interaction whereas high cellular respiration, induced by adding the mitochondrial uncoupler FCCP, prevented interaction. UCP2 KD contributed to increased carboxyatractyloside (CATR) sensitive proton leak, whereas ANT2 and UCP2 double KD reduced CATR sensitive proton leak, compared to UCP2 KD. Furthermore, proton leak was reduced in double KD compared to UCP2 KD. In conclusion, our results show that there is an interaction between ANT2-UCP2, which appears to be dynamically regulated by mitochondrial respiratory activity. This may have implications in the regulation of mitochondrial efficiency or cellular substrate utilization as increased activity of UCP2 may promote a switch from glucose to fatty acid metabolism.